An Empirical Analysis of the IPO Underpricing Phenomenon In China Market (2006-2011) - Lu, Tianshu (2012)
This study investigates the underpricing phenomenon of initial public offerings (IPO) on Chinese A-share market by using a sample consisting of 991 IPOs from June 2006 to December 2011. The average underpricing for A-share is 66% which considerably decreases than other studies of China. Previous studies on China’s IPO underpricing have been suggestive, but inconclusive due to Chinese specific feature and government intervention. The results of this study suggests that winner’s curse has a relatively weak support to explain phenomenon in China, and inequality of demand and supply is still the main factor which influences the underpricing level in China. Especially demand in secondary market and overreaction of investors are regarded to be a dominate factors leading to high price of IPOs. In addition, Security companies had been introduced as underwriters in China’ new issuing process, the testing result of underwriters’ reputation effect implies that the incomplete system for underwriters in China and requesting for further development at underwriters’ side with the help of the central regulatory. Study also finds the ‘equity separation reform’ to some extent aggravated the level of underpricing. Afterwards, after financial crisis, the underpricing level considerably decreased, in the meantime the establishment of ChiNext booms the trading volume of A-share market. Finally, the study concludes that the decreasing numbers of non-listed big-companies could give opportunities to SMEs Board and ChiNext.